2016
DOI: 10.3390/app7010033
|View full text |Cite
|
Sign up to set email alerts
|

Improving Corrosion Resistance and Biocompatibility of Magnesium Alloy by Sodium Hydroxide and Hydrofluoric Acid Treatments

Abstract: Abstract:Owing to excellent mechanical property and biodegradation, magnesium-based alloys have been widely investigated for temporary implants such as cardiovascular stent and bone graft; however, the fast biodegradation in physiological environment and the limited surface biocompatibility hinder their clinical applications. In the present study, magnesium alloy was treated by sodium hydroxide (NaOH) and hydrogen fluoride (HF) solutions, respectively, to produce the chemical conversion layers with the aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Moreover, the Cl − ion in the solution can decompose the Mg(OH) 2 film and convert it into soluble magnesium chloride (MgCl 2 ). Therefore, Mg(OH) 2 coating as a physical barrier can successfully separate the Mg substrate from an aqueous solution or physiological environment, but is not sufficient to endow Mg alloys with long-term corrosion resistance [ 109 ]. Mg(OH) 2 film is often used as an inner layer for augmenting the adhesion between the Mg substrate and the outer layer.…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the Cl − ion in the solution can decompose the Mg(OH) 2 film and convert it into soluble magnesium chloride (MgCl 2 ). Therefore, Mg(OH) 2 coating as a physical barrier can successfully separate the Mg substrate from an aqueous solution or physiological environment, but is not sufficient to endow Mg alloys with long-term corrosion resistance [ 109 ]. Mg(OH) 2 film is often used as an inner layer for augmenting the adhesion between the Mg substrate and the outer layer.…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“… Mg–Zn TiO 2 0.400 SBF −1.70 −1.65 1050 49.0 23.99 1.119 14 TiO 2 film had a low HR (1%) and inhibited platelet adhesion and promoted ECs attachment [ 91 ]. AZ31B Mg(OH) 2 SBF −1.57 −1.174 37.26 2.052 0.851 0.046 7 MgF 2 coating had relatively better corrosion resistance than Mg(OH) 2 coating, however, Mg(OH) 2 coating showed better anti-thrombosis and cytocompatibility to ECs than MgF 2 coating [ 109 ]. MgF 2 −1.128 0.6821 0.015 JDBM Mg 3 (PO 4 ) 2 3.5 Artificial plasma −1.74 −1.63 1.59 1.08 0.036 0.024 The prepared phosphate coating improved the corrosion resistance and biological response.…”
Section: Surface Modification Of Mg Alloy Stentsmentioning
confidence: 99%
“…On the other side, it is well known that the fluoride element generally exhibits hydrophobicity. The magnesium fluoride layer can not only resist the substrate from the corrosion medium but also provide a hydrophobic surface to prevent the corrosion ions from penetrating into the magnesium substrate, leading to the enhanced corrosion resistance [14]. Figure 3: SEM image of AZ31 Mg alloy after pickling for 1 min.…”
Section: Figure 2: Optical Microscopic Photograph Of Mg Alloy After Pmentioning
confidence: 99%
“…Several studies [16][17][18][19][20][21] have shown that the fluoride conversion coating is suitable for protecting the biodegradable magnesium alloys against corrosion in biological environments while the coating is acceptable for the human body. The preparation of fluoride conversion coating can be based on dipping the magnesium alloy into the HF solution [16][17][18]22,23] or the less used way based on dipping the magnesium alloy into Na [BF 4 ] molten salt [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%